A Case of Retinal Tear Associated with Use of Sorafenib - Gaertner, Kelly M.; Caldwell, Stephen H.; Rahma, Osama E. (Frontiers in Oncology, 2014)
Inhibition of angiogenesis is a target in the treatment of a variety of malignancies. Sorafenib is an oral inhibitor of multiple tyrosine kinases involved in tumor angiogenesis. A related case of ophthalmologic toxicity has been reported with another vascular endothelial growth factor receptor inhibitor, sunitinib. We report the first case of retinal tear possibly associated with sorafenib.